2012
DOI: 10.1292/jvms.10-0289
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Testosterone and Inhibin Levels at Different Ages in the Male Beluga (<i>Delphinapterus leucas</i>)

Abstract: ABSTRACT. This study is the first report on circulating testosterone and inhibin levels in a species of whales, the beluga. Circulating testosterone and immunoreactive (ir-) inhibin levels in two captive male belugas ("Nack", originally from Canada and "Duke", from the Okhotsk Sea) were measured every month for 9 years between 1995 and 2003. Assuming that clearly increased testosterone levels in the circulation indicates that the belugas had reached sexual maturity, at the ages of 10 ("Nack") and 11 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The circulating inhibin concentrations in Oscar were high in the juvenile stage and declined abruptly after sexual maturity. This dramatic change in circulating inhibin concentrations showed a clear negative correlation with testosterone during the mature stage, confirming previous reports in beluga (Delphinapterus leucas) (Katsumata et al, 2012) and bottlenose dolphins (Tursiops truncatus) (Katsumata et al, 2017). Importantly, the same high concentrations of circulating inhibin prior to sexual maturity coupled with low concentrations thereafter have been observed also in terrestrial mammals, such as bull calves (Kaneko, et al, 2001, Matsuzaki, et al, 2000, 2001a, 2001b, boars (Kanematsu et al, 2006), and horses (Dhakal et al, 2011(Dhakal et al, , 2012.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The circulating inhibin concentrations in Oscar were high in the juvenile stage and declined abruptly after sexual maturity. This dramatic change in circulating inhibin concentrations showed a clear negative correlation with testosterone during the mature stage, confirming previous reports in beluga (Delphinapterus leucas) (Katsumata et al, 2012) and bottlenose dolphins (Tursiops truncatus) (Katsumata et al, 2017). Importantly, the same high concentrations of circulating inhibin prior to sexual maturity coupled with low concentrations thereafter have been observed also in terrestrial mammals, such as bull calves (Kaneko, et al, 2001, Matsuzaki, et al, 2000, 2001a, 2001b, boars (Kanematsu et al, 2006), and horses (Dhakal et al, 2011(Dhakal et al, , 2012.…”
Section: Discussionsupporting
confidence: 89%
“…However, one of the testicular hormones, inhibin has not been investigated in male killer whales. Inhibin is a glycoprotein hormone secreted by the gonads in mammals (Medan et al, 2007, Chaichanathong et al, 2017, birds (Akashiba et al, 1988, Yang et al, 2005a, 2005b, 2005c, and some Cetaceans, such as beluga (Katsumata et al, 2012) and bottlenose dolphin (Katsumata et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are only a few studies that have been dedicated to investigating cetacean inhibin levels. Katsumata et al [ 13 ] determined serum testosterone and inhibin levels in two captive belugas ( Delphinapterus leucas ) and demonstrated that these two hormones are negatively correlated and inhibin levels were higher in the sexually immature stage than in the mature stage. In the present study, changes in testicular functions during the growth process of male captive bottlenose dolphins ( Tursiops truncatus ) were revealed by measurements of circulating gonadotropins (FSH and LH) and testicular hormones (testosterone and inhibin) in blood samples taken from two male captive bottlenose dolphins reared at Kamogawa Sea World in Japan for 8 and 12 years.…”
Section: Discussionmentioning
confidence: 99%